Homework in the primary school - Students' perception - Lopes, Mónica (2022)
Homework is one of the most widespread but controversial strategies used in the first school years. Students’ opinion and commitment tohomework vary between them. Students’ perception of homework and how variables such as sex or perceived difficulties influence it wereinvestigated in this work. For that, a descriptive, correlational, cross-sectional survey was performed on 282 primary school’s students ofViseu, Portugal. Data analysis shows that all students perform homework and their opinion about it is mostly favorable. Statistical analysis reveals an association between students’ feelings about homework, their decision to perform them, and the time spend on them. Associationsbetween some of the variables were also observed with students’ sex. Male students like homework lesser and more frequently would decidenot to perform it. On the other hand, female students reveal more difficulties on mathematic and usually have help doing homework. Acluster analysis revealed three types of students: a small group who does not like and does not understand the importance of homework butdo not present difficulties, a group who likes homework and think they are important but have difficulties in its performance, and finally agroup who likes homework and does not have performance’s difficulties. Recognition of these three types of students could help educatorschoosing different homework strategies for each group, for instance, altering the kind of homework requested or its difficulty.